2021
DOI: 10.1038/s41531-021-00155-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of brain perivascular space burden in early-stage Parkinson’s disease

Abstract: Perivascular space (PVS) is associated with neurodegenerative diseases, while its effect on Parkinson’s disease (PD) remains unclear. We aimed to investigate the clinical and neuroimaging significance of PVS in basal ganglia (BG) and midbrain in early-stage PD. We recruited 40 early-stage PD patients and 41 healthy controls (HCs). Both PVS number and volume were calculated to evaluate PVS burden on 7 T magnetic resonance imaging images. We compared PVS burden between PD and HC, and conducted partial correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 68 publications
1
45
0
Order By: Relevance
“…Their results suggested an association between EPVS and SN degeneration in PD ( Li et al, 2020 ). Another study also showed that patients with PD had a higher PVS burden in BG and midbrain than NCs, and the PVS number in BG significantly correlated with disease severity and L -dopa equivalent dosage ( Shen et al, 2021 ). We speculated that a reduced glymphatic activity results in the accumulation of the misfolding proteins such as α-syn, which is implicated in the development of PVS dilation on MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Their results suggested an association between EPVS and SN degeneration in PD ( Li et al, 2020 ). Another study also showed that patients with PD had a higher PVS burden in BG and midbrain than NCs, and the PVS number in BG significantly correlated with disease severity and L -dopa equivalent dosage ( Shen et al, 2021 ). We speculated that a reduced glymphatic activity results in the accumulation of the misfolding proteins such as α-syn, which is implicated in the development of PVS dilation on MRI.…”
Section: Discussionmentioning
confidence: 99%
“…P ARKINSON'S disease (PD) is a chronic neurodegenerative disorder without pathologic treatment, characterized by motor symptoms (resting tremor, bradykinesia, rigidity and abnormal gait) and non-motor symptoms (depression, anxiety, cognitive decline, etc.) [1]- [3]. Patients usually need to seek treatment after 50 to 80% of the Substantia Nigra pars compacta (SNc) has been destroyed [4].…”
Section: Introductionmentioning
confidence: 99%
“…NPVSs are typically invisible due to small size in the range of 0.13-0.96 mm [ 39 ]. Seven Tesla (7T) MRI, with increased spatial resolution and signal-to-noise ratio, increases the detection of nPVSs [ 40 , 41 ]. The 7T sequences have been optimized to provide detailed assessment of distributions of nPVSs in the white matter and subcortical nuclei [ 42 ].…”
Section: Introductionmentioning
confidence: 99%